Characterization of Intra‐ and Intermolecular Protein Crosslinking by Top Down Ultraviolet Photodissociation Mass Spectrometry. Issue 3 (22nd March 2016) - Cammarata, Michael B.; Brodbelt, Jennifer S.
Abstract: Interactions within and between proteins impact structure and function, and mapping these interactions is a key hallmark of structural proteomics. One popular method for mapping protein interactions utilizes homobifunctional crosslinkers with defined distance constraints, followed by bottom‐up mass spectrometry analysis. In this study, characterization of protein crosslinks was accomplished by top‐down mass spectrometry (MS) using both ultraviolet photodissociation (UVPD) and higher energy collisional dissociation (HCD) in conjunction with reversed phase nanoscale liquid chromatography (nanoLC). Four intramolecular crosslinks of ubiquitin were identified, all in agreement with the known tertiary structure. Three intermolecular crosslinks of insulin were unambiguously assigned, consistent with the hexameric complex adopted by insulin in solution. This integrated top‐down nanoLC/UVPD/HCD‐MS approach affords a powerful strategy for deciphering details about tertiary structure and intermolecular protein interactions. Abstract : Top‐down mass spectrometry using ultraviolet photodissociation (UVPD) and higher energy collisional activation (HCD) in conjunction with nanoscale reversed phase chromatography was developed to identify intra‐ and intermolecular crosslinks. Four intra‐ and three inter‐protein crosslinks were elucidated for ubiquitin and hexameric insulin, respectively. This approach offers a compelling strategy for mapping protein interactions.